2010
DOI: 10.1016/j.jjcc.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Soluble lectin-like oxidized LDL receptor-1 (sLOX-1) as a sensitive and specific biomarker for acute coronary syndrome—Comparison with other biomarkers

Abstract: Circulating sLOX-1 is a more sensitive and specific biomarker for ACS than TnT and H-FABP, and provides additional diagnostic values when measured in combination with TnT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 36 publications
(50 reference statements)
4
50
0
Order By: Relevance
“…In fact, a previous study has shown that sLOX-1 was able to detect ACS in cases in which TnT levels measured by a conventional assay were not increased during the acute stage, with similar sensitivity and specificity to the values determined for the whole population. 19 In the present study, in which the negative reference was non-ACS patients with similar chest symptoms and ECG abnormalities in the ER, we demonstrated, for the first time, that sLOX-1 was able to detect ACS during the acute stage in cases in which the hs-TnT levels were not increased, with similar sensitivity and specificity to those in the whole population.…”
Section: 15-18supporting
confidence: 60%
“…In fact, a previous study has shown that sLOX-1 was able to detect ACS in cases in which TnT levels measured by a conventional assay were not increased during the acute stage, with similar sensitivity and specificity to the values determined for the whole population. 19 In the present study, in which the negative reference was non-ACS patients with similar chest symptoms and ECG abnormalities in the ER, we demonstrated, for the first time, that sLOX-1 was able to detect ACS during the acute stage in cases in which the hs-TnT levels were not increased, with similar sensitivity and specificity to those in the whole population.…”
Section: 15-18supporting
confidence: 60%
“…The sLOX-1 levels have been shown to significantly increase in atherosclerotic plaque instability [23], diabetes mellitus [19], obesity [18], and are positively correlated with a reduction in body weight [24]. Association with coronary artery disease and metabolic disorders also suggested sLOX-1 as a biomarker for early detection of acute coronary syndrome [25,26]. We therefore sought to assess whether serum sLOX-1 levels could be used as an index of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Level of sLOX-1 was a more specific and sensitive biomarker of ACS than others such as cardiac troponin T (cTnT), heart type-fatty acid binding protein, and high sensitive C-reactive protein [26,29]. The sLOX-1 was recommended as a suitable marker for early diagnosis of ACS than cTnT because 86% of the cTnT-negative patients showed sLOX-1 levels >1.0 ng/mL serum.…”
Section: Discussionmentioning
confidence: 99%
“…LOX-1 is expressed on the cell surface and can be proteolytically cleaved at its extracellular domain and released as a soluble form (sLOX-1) ( 6 ). sLOX-1 level refl ects increased oxidative stress of vascular walls and has been identifi ed as a novel marker for early diagnosis of ACS ( 7,8 ). However, the exact mechanisms of sLOX-1 release from the cell membrane are poorly understood.…”
mentioning
confidence: 99%